ANALISIS PERENCANAAN PEMBELAJARAN GEOGRAFI BERBASIS HOTS DI SMA NEGERI I LEMBAH GUMANTI - aulia rusda; Khairani Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
his study aims to determine the extent of the design of the Learning Implementation Plan (RPP) at SMAN I Valley Gumanti containing indicators of high-level thinking skills. This type of research is descriptive with a qualitative approach that uses documents as the object of study. The data or data source used in this research is the RPP of Geography learning teachers. The research instrument, the researcher himself as an instrument that uses the documentation method, and subsequent interviews the data analysis technique used is a descriptive qualitative data analysis technique. Based on the analysis of the RPP of teachers in Geography learning in the 2019-2020 school year Odd Semester learning steps. However, the GPA is determined by the level of operational verbs (KKO) used, namely C1-C3 is LOTS / MOTS and C4-C6 is HOTS. Which is not yet fully in the HOTS category.